Low-cost Space Varying FIR Filter Architecture for Computational Imaging Systems - Feng, Guotong; Zarar, Shuayb; Schwartz, Edward; Robinson, Dirk (SPIE Digital Photography VI, 2010)
Recent research demonstrates the advantage of designing electro-optical imaging systems by jointly optimizing the optical and digital subsystems. The optical systems designed using this joint approach intentionally introduce large and often space-varying optical aberrations that produce blurry optical images. Digital sharpening restores reduced contrast due to these intentional optical aberrations. Computational imaging systems designed in this fashion have several advantages including extended depth-of-field, lower system costs, and improved low-light performance. Currently, most consumer imaging systems lack the necessary computational resources to compensate for these optical systems with large aberrations in the digital processor. Hence, the exploitation of the advantages of the jointly designed computational imaging system requires low-complexity algorithms enabling space-varying sharpening. In this paper, we describe a low-cost algorithmic framework and associated hardware enabling the space-varying finite impulse response (FIR) sharpening required to restore largely aberrated optical images. Our framework leverages the space-varying properties of optical images formed using rotationally-symmetric optical lens elements. First, we describe an approach to leverage the rotational symmetry of the point spread function (PSF) about the optical axis allowing computational savings. Second, we employ a specially designed bank of sharpening filters tuned to the specific radial variation common to optical aberrations. We evaluate the computational efficiency and image quality achieved by using this low-cost space-varying FIR filter architecture.